Peranan Komunikasi Antar Personal Mahasiswa Kost Terhadap Nilai - Nilai Kemasyarakat - Aliyandi Aiylandi (Ath Thariq Jurnal Dakwah dan Komunikasi, 2017)
The desire of mankind to live full of serenity and peace will never be realized if acts of terror, greed, injustice, and whatever form that represents a sanity still remain grounded. History has noted that acts of terrorism and violence, not a problem solving, but make complicated and increasing a problem. Terrorism is a form of extraordinary crime (extra ordinary crime). In an effort to prevent the understanding of terrorism that becomes the enemy of the state and also the religious community, the government or the security side must also coordinate with the scholars, da'i and community figures in order that the society and the country are getting away from munkar. The government and society should not allow rampant injustice and socio-economic imbalance. Therefore, according to Nur Syam really needed is the integration between hard power and soft power to overcome this religious radicalism. The hard power represented by government is essentially to cope instantaneously or to cope quickly with the radical movement. But far more important is the role of soft power or community - including APDI (Association of Indonesian Dakwah Profession) - to carry out guidance and community development that puts Islamrahmatan lil alamin forward.